Oswald Veblen papers - Veblen, Oswald, 1880-1960.
Correspondence, diaries, drafts of books, articles, book reviews, lecture notebooks, subject files, financial records, photographs, and other papers primarily concerning Veblen's career in pure mathematics and mathematical physics and reflecting his associations with the American Mathematical Society, the Institute for Advanced Study (Princeton, N.J.), and Princeton University. Also includes material relating to the founding of Mathematical Reviews and to Veblen's efforts on behalf of displaced German scholars and other refugees. Correspondents include James W. Alexander, George David Birkhoff, Niels Bohr, P.A.M. Dirac, Albert Einstein, Abraham Flexner, Robert Andrews Millikan, O. Neugebauer, J. Robert Oppenheimer, Linus Pauling, O.W. Richardson, R.G.D. Richardson, Bertrand Russell, Marshall H. Stone, Lewis L. Strauss, Dirk J. Struik, John von Neumann, Hermann Weyl, John Henry Constantine Whitehead, Norbert Wiener, and Eugene Paul Wigner.
Mathematician.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Alexander, James W., -- 1888-1971 -- Correspondence; Birkhoff, George David, -- 1884-1944 -- Correspondence; Bohr, Niels, -- 1885-1962 -- Correspondence; Dirac, P. A. M. -- 1902-1984 -- Correspondence; Einstein, Albert, -- 1879-1955.; Flexner, Abraham, -- 1866-1959.; Millikan, Robert Andrews, -- 1868-1953.; Neugebauer, O. -- 1899-1990.; Oppenheimer, J. Robert, -- 1904-1967.; Pauling, Linus, -- 1901-1994.; Richardson, O. W. -- 1879-1959 -- Correspondence; Richardson, R. G. D. -- 1878-1949 -- Correspondence; Russell, Bertrand, -- 1872-1970 -- Correspondence; Stone, Marshall H. -- 1903- -- Correspondence; Strauss, Lewis L. -- Correspondence; Struik, Dirk J. -- 1894-2000 -- Correspondence; Von Neumann, John, -- 1903-1957 -- Correspondence; Weyl, Hermann, -- 1885-1955 -- Correspondence; Whitehead, John Henry Constantine, -- 1904-1960 -- Correspondence; Wiener, Norbert, -- 1894-1964 -- Correspondence; Wigner, Eugene Paul, -- 1902- -- Correspondence; American Mathematical Society; Institute for Advanced Study (Princeton, N.J.); Princeton University; Mathematical reviews; Mathematical physics; Mathematics; Mathematics -- Societies, etc; Refugees -- United States; Science -- History -- 20th century; Universities and colleges -- New Jersey; Mathematicians